Pembinaan Karakter Melalui Pembelajaran Pendidikan Agama Islam pada Siswa Kelas IV SDN Kip Bara-Baraya II Kota Makassar - Musbaing Musbaing; Nurlaili Nurlaili (AIJER: Algazali International Journal Of Educational Research, 2021)
Abstract: Character Building Through Learning Islamic Religious Education pthere are Grade IV Students of SDN Kip Bara-Baraya II Kota Makassar. This study aims to find out character building through learning Islamic religious education pthere are Grade IV students of SDN Kip Bara-Baraya II Kota Makassar. The approach used in this research uses a qualitative approach, with the type of field research. The data analysis method used in this study is qualitative analysis, with the use of inductive reasoning. To determine the validity of the data, researchers use data trianggulation techniques. The results of the study show that character building through PAI learning in grade IV students at SDN Kip Bara-Baraya II is by developing character building values through pai learning among others: 1) faith and piety, 2) morality, 3) self-confidence, 4) thrifty, 5) discipline.